Domestic Tax Planning: Tax Avoidance and Tax Evasion - Sharla Martiza, Berlika; Santoso, Rizki Agung; Fuadah, Luk Luk (Dinasti Publisher, 2025)
Domestic tax planning has become a central topic in global tax discussions, particularly in the context of tax avoidance and tax evasion. Tax avoidance refers to legally but aggressively reducing tax obligations, whereas tax evasion involves illegal actions aimed at evading taxes. This study aims to systematically review recent research on domestic tax planning using the Systematic Literature Review (SLR) method. Data were collected from 100 reputable journals published between 2019 and 2024 and analyzed using a thematic approach. The findings indicate that executive characteristics, tax morale, and corporate social responsibility (CSR) play significant roles in tax planning strategies. Moreover, complex tax regulations in developed countries tend to drive more sophisticated tax planning schemes, while in developing countries, a lack of transparency and oversight increases the likelihood of tax evasion. This study emphasizes that tax planning can provide economic benefits for companies but also poses reputational risks. Regulators need to strengthen tax policies to limit tax evasion without hindering legitimate tax planning. Future research is expected to explore the impact of technology on tax strategies and the effectiveness of more transparent and accountable tax policies.